India : Staff Report for The 2015 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that India's near-term growth outlook has improved, and the balance of risks is now more favorable, helped by increased political certainty, several positive policy actions, improved business confidence, and reduced external vulnerabilities. Growth is projected at 5.6 percent for FY 2014/15, picking up to 6.3 percent in FY 2015/16, as a result of the revival in industrial and investment activity. However, weaknesses in India's corporate and bank balance sheets will weigh on credit growth, and fiscal restraint and a tight monetary stance will act as headwinds in the near term, offsetting the positive growth impact of the improved commodity terms of trade.